Male Aggregation in Dwarf Tyrant-Manakins and What It Tells Us about the Origin of Leks. (23rd March 2021) - Foster, Mercedes S
Synopsis: Despite considerable research on lek-breeding birds, many aspects of the evolution of the lek social system, including the origin of male aggregation, remain unresolved. Originally, clusters may have formed passively as a by-product of independent but concurrent responses by males to some external stimulus (e.g., a concentration of display sites, prominent food source, or a travel corridor commonly used by females) that drew them at a particular time to a site where they might increase their probabilities of encountering females. In contrast, male aggregation may have been active, with a male purposely seeking to associate with another male (or males) because proximity to that male allowed him to enhance his own reproductive success by improving his ability to attract females (i.e., learning from his associate) or to intercept females attracted to that male. To identify factors important in the formation of male aggregations, I studied these alternatives in the Dwarf Tyrant-Manakin ( Tyranneutes stolzmanni ), a species in which some breeding males occupy solitary courts where they attempt to attract females for reproduction, whereas other males occupy courts clustered into leks, where they interact to attract females. I compared habitat characteristics and resource availability at courts of grouped and solitary males as well as certain traits of the males in an attempt to distinguish between passive or active lek formation in this species. Little evidence suggests that Dwarf Tyrant-Manakins are passively clustered as a result of common attraction to or use of a limited or unevenly distributed resource. Several observations suggest the contrary. Evidence for the active aggregation of males is more promising, suggesting that males may associate with other males on the basis of their vocal behavior. The issue is confounded, however, by the observation that male call behavior appears to change with a change in social status. A definitive answer for T. stolzmanni will require additional analyses of vocal behavior as well as of the characteristics of the vocalizations themselves. Finally, the behavior and social organization of this species may reflect characteristics of the ancestral manakin line that gave rise to both the Tyrant and Core clades of modern manakins.